THE GREEN APPROACH FOR THE SYNTHESIS OF SOME HYDROQUINOLINE DERIVATIVES COMPOUND VIA HANTZSCH REACTION - Othman, Layla Ahmed (Science Journal of University of Zakho, 2024)
Since that hydroquinoline and acridine compounds serve as the fundamental building blocks for the synthesis of many different pharmaceuticals, they are among the most significant classes of chemical compounds that attract the interest of numerous researchers and pharmacologists. Therefore, in this research, The Hantzch reaction was used to prepare these types hydroquinoline and acridine derivatives of compounds, through the reaction of a number substituted benzaldehyde with demidone and α-β diketone substitutes by refluxed with sodium acetate in the presence of iodine and a 1-sulfo-4-(3-(Ferricoxide-Silicondioxide nanopowdertrioxisilyl)propyl) piperazinum-1,4-diphosphate as a catalyst to form 7,7- dimethyl -4,6,7,8-tetrahydroquinoline derivatives which is represented by compounds (1-12) or in the same way by react benzaldehyde substitutes react with demidone and 4-isopropyl cyclohexanone 1-one to form acridin derivatives represented by compounds (13 -17). All product compound are characterized using 1H-NMR spectra and the results confirmed the structures.